Intimate connections between music, education and play in Plato's dialogues - Avanco, Leonardo Dias [UNESP]; Lima, Jose Milton de [UNESP] (Univ Federal Ceara, Geography Posgraduate Program, 2021)
By revisiting important hermeneutic aspects of platonic philosophy, this article aims to provide an orientation with regard to the cultural fecundity of certain reintegrations of three types of human activity, among which solid barriers have been often pursued recently: play, education and music. This text is exposed in two parts, where the first part comprises points of balance between the concept of play and education, while the second part examines and interprets the paradox of fight in philosophy and poetry in Plato's Dialogues, from an enhancement of the notion of music. The agreement between the two parts resides on the ludic and educational bases of ancient poetry and philosophy. Finally, for the purpose of the conclusion, a general orientation is proposed as the synthesis of the conjectures, argumentations, and demonstrations elaborated under the light of the examples present in the platonic work.
Keywords: Ludicity; Philosophy; Art; Formation; Science